High-Performance Standalone Photovoltaic Water Pumping System Using Induction Motor. (18th August 2020) - Errouha, Mustapha; Derouich, Aziz; El Ouanjli, Najib; Motahhir, Saad
Abstract : This work is aimed at achieving a simple and reduced-cost configuration of photovoltaic (PV) water pumping system (PVWPS) using an induction motor with high efficiency. The proposed PV system is composed of two stages of converters which the first one ensures the maximum power point by controlling the duty ratio of boost converter using variable step size incremental conductance (VSS INC) technique. Fuzzy logic control based on direct torque control is proposed to serve the purpose of operating an induction motor. Moreover, the combining of these proposed control strategies has been never discussed. The proposed control scheme is modeled and simulated in detail under MATLAB/Simulink software to evaluate its performance under fast variations of irradiance and daily climatic profile. The obtained simulation results using the suggested control strategies are compared to those using the most used method in the literature (variable step size perturb and observe (VSS P&O) algorithm). The simulation results indicate that the proposed PVWPS performed best in terms of the time of response; pumped water, flux ripples, and the stator currents are reduced.